Recording, storing and querying judo match data using an Android tool and Cloud computing - Villapol, M. E.; Jansen, H.; Morales, A.; Flores, J.; Rodrigues, H.; Huerta, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Judo is a martial art that was created as a physical, intellectual and moral education method in Japan. In competition matches, Judo is a combat sport where two athletes fight against each other. Judo matches are ruled by different scores, penalties and durations, which change regarding the age and gender of the competitors. There is a need to record the actions in favour of or against a judoka during a match in order to create an efficient training programme as well as technical and tactical development strategies for each competitor. In this work, a technological solution is presented; it records each athlete`s matches and scores, penalties, pauses during the match and its actual length of time. These aspects can help to create charts reflecting efforts made by the judoka. The research is focused on the support of the technical-tactical analysis of judo matches, taking into account recent information technology and communications trends: (1) the solution is developed for mobile devices which use the Android operating system, (2) the solution takes advantage of Cloud computing to allow ubiquitous access to the data and (3) the desktop component of the solution is portable to many computer systems because it has been developed using the Java programming language. The initial results show how the technological solution can be used for improving the performance of the athlete by providing feedback of the behaviour of the judoka during each match.